Mechanical characteristics of spinal cord tissue by indentation - Neumann, Oskar; Surana, Harsh Vardhan; Melly, Stephen Kirwa; Steinmann, Paul; Budday, Silvia (Journal of the Mechanical Behavior of Biomedical Materials, 2025)
The mechanical properties of brain and spinal cord tissue have proven to be extremely complex and difficult to assess. Due to the heterogeneous and ultra-soft nature of the tissue, the available literature shows a large variance in mechanical parameters derived from experiments. In this study, we performed a series of indentation experiments to systematically investigate the mechanical properties of porcine spinal cord tissue in terms of their sensitivity to indentation tip diameter, loading rate, holding time, ambient temperature along with cyclic and oscillatory dynamic loading. Our results show that spinal cord white matter tissue is more compliant than grey matter tissue with apparent moduli of 128.7 and 403.8 Pa, respectively. They show similar viscoelastic behavior with stress relaxation time constants of τ1 = 1.38 s and τ2 = 36.29 s for grey matter and τ1 = 1.46 s and τ2 = 46.10 s for white matter, while the initial peak force decreased by 54 % for grey and 59 % for white matter tissue. An increase of the applied loading rate by two orders of magnitude led to an approximate doubling of the apparent modulus for both tissue types. Thermal variations showed a decrease in apparent modulus of up to 30 % after heating from 20 to 37.0 °C. Our dynamic tests revealed a significant influence of cyclic preload on the stiffness, with a drop of up to 20 % and a relative decrease of up to 60 % after the first cycle compared to the total modulus drop after five cycles for spinal cord grey matter tissue. Oscillatory indentation experiments identified similar loss moduli for spinal cord grey and white matter tissue and a higher storage modulus for white matter tissue. This work provides systematic insights into the mechanical properties of spinal cord tissue under different loading scenarios using nanoindentation.<br
Keywords: Spinal cord; Grey matter; White matter; Nanoindentation; Viscoelasticity; Dynamic properties; Thermomechanical properties